2009
DOI: 10.1210/jc.2008-0923
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Chemotherapy of Differentiated Epithelial and Medullary Thyroid Cancers

Abstract: Context: Systemic chemotherapies for advanced or metastatic thyroid carcinomas have been of only limited effectiveness. For patients with differentiated or medullary carcinomas unresponsive to conventional treatments, novel therapies are needed to improve disease outcomes.Evidence Acquisition: The PubMed and Google Scholar search engines were used to identify publications and peer-reviewed meeting presentations addressing chemotherapy and targeted therapy for differentiated or medullary carcinoma.Evidence Synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 70 publications
(70 reference statements)
0
62
0
Order By: Relevance
“…However, it has been demonstrated that this mutation is refractory to many tyrosine kinase inhibitors (TKI) (35), which nowadays are considered the best target therapy under development (36). It is of concern that if Val804Met mutation is so prevalent, some of these patients might develop an aggressive form with no possibility of being treated with TKI.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been demonstrated that this mutation is refractory to many tyrosine kinase inhibitors (TKI) (35), which nowadays are considered the best target therapy under development (36). It is of concern that if Val804Met mutation is so prevalent, some of these patients might develop an aggressive form with no possibility of being treated with TKI.…”
Section: Discussionmentioning
confidence: 99%
“…The specific factors and requirements for angiogenesis and blood vessel formation may vary in different organs. Many of the current treatments that have shown disease-stabilizing effects in metastatic thyroid cancer are thought to inhibit metastasis-related angiogenesis by inhibiting responses to vascular endothelial growth factor (VEGF) (36). However, whether or not VEGF receptors are the primary target of the compounds clinically has not been proven.…”
Section: Angiogenesismentioning
confidence: 99%
“…Therefore, such dependency may represent a potential Achilles heel of cancer cells. Since thyroid cancer cells are apparently "addicted" to aberrant MAP kinase signalling, several small molecules that target this pathway are currently being developed (Sherman, 2009). Several lines of evidence suggest that RET/PTC can be a good target.…”
Section: Targeted Therapy Of Thyroid Cancermentioning
confidence: 99%